The Important Role of Emotional Intelligence to Face Competitive Business - Adisti Prita Andiani; Dhia Qomara Rizani; Rosa Khoirunnisa; Khairunnisak Khairunnisak (Institut Teknologi Sepuluh Nopember, 2020)
For now, emotional intelligence is a hot topic to discuss, but how important is the emotional intelligence for organisation. To find the answer, this research widen the concept of emotional intelligence in competitive business world. Today, given the progress of the nature business world is highly competitive, it is important for bussinesmen to be more creative, innovative, initiative, and optimistic so they can deal with misfortunes events and defeats. The paper takes the form of an examination of the relevant literature and divergent thinking from related topic emotional intelligence and competitive business. Researchers found skill is a core element for each candidate to be a better individual, especially in the business world. Emotional intelligence is something entrepreneur and leader must possed. Emotional intelligence helps us to be more confident, socially enggaged, motivated, well-controlled, open minded in communicating, and also can make us more successful. Thus, it helps to estabilish healthier communication that can be used to reduce conflict within the organisation